Immunohistochemical analysis of the neural structures of the posterior cruciate ligament in osteoarthritis patients submitted to total knee arthroplasty: an analysis of thirty-four cases (Clinics, 2015)
OBJECTIVES: Many authors recommend posterior cruciate ligament-retaining arthroplasty with the intention to maintain the proprioception properties of this ligament. Preservation of the neuroreceptors and nervous fibers may be essential for retaining the proprioception function of the posterior cruciate ligament. The present study was thus developed to evaluate the presence of neural structures in the posterior cruciate ligament resected during posterior stabilized arthroplasty in osteoarthritis patients. In particular, clinical, radiographic and histological parameters were correlated with the presence or absence of neural structures in the posterior cruciate ligament. METHODS: In total, 34 posterior cruciate ligament specimens were stained with hematoxylin-eosin and Gomori trichrome. An immunohistochemical analysis using antibodies against the S100 protein and neurofilaments was also performed. The presence of neural structures was correlated with parameters such as tibiofemoral angulation, histological degeneration of the posterior cruciate ligament, Ahlbäck radiological classification, age, gender and the histologic pattern of the synovial neurovascular bundle around the posterior cruciate ligament. RESULTS: In total, 67.5% of the cases presented neural structures in the posterior cruciate ligament. In 65% of the cases, the neurovascular bundle was degenerated. Nervous structures were more commonly detected in varus knees than in valgus knees (77% versus 50%). Additionally, severe histologic degeneration of the posterior cruciate ligament was related to neurovascular bundle degeneration. CONCLUSIONS: Severe posterior cruciate ligament degeneration was related to neurovascular bundle compromise. Neural structures were more commonly detected in varus knees. Intrinsic neural structures were detected in the majority of the posterior cruciate ligaments of patients submitted to knee arthroplasty for osteoarthritis.